A Cost–Benefit Analysis of Summer Reading Programs Implemented Under State Guidelines. Issue 4 (June 2020) - Reed, Deborah K.; Cook, Kevin M.; Aloe, Ariel M.
This study investigated the costs of different summer reading programs and compared costs to the benefits of summer school as a way to avoid retaining students not reading proficiently at the end of third grade. Per pupil costs ranged from US$1, 665 to US$2, 194. The average cost was US$1, 887 (range: US$266-US$5, 552) with 82% of overall expenses attributable to personnel. Results indicate that offering summer reading programs could save schools across the state a total of between US$70.6 million and US$75.5 million in expenses related to providing an extra year of school had all eligible students been retained in third grade instead. This equates to about US$4 in benefit for every dollar invested in summer programs.